Nilai-Nilai Universal Politik Islam dalam Suksesi Kepemimpinan Khalifah Abu Bakar Ash-Shiddiq - Zanilha, Muflihah; Ramadhani, Wahdania; Aswal. K; Kurniati (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
The values ​​of Islamic political ethics in the context of Abu Bakar’s leadership succession are an important moment in Islamic history. Abu Bakr is known as the first caliph after the death of the Prophet Muhammad SAW, and his election process reflects the values ​​of political ethics in Islam. This research aims to identify the universal values ​​of Islamic political ethics that are reflected in the leadership process of Abu Bakar Ash-Siddiq and their relevance in the context of modern leadership that can be applied in the political system. This research explores Abu Bakar’s principles of justice, deliberation, responsibility and sincerity. This research uses a qualitative approach with a literature study method, by examining various literary sources that discuss leadership succession in Islam and especially about Abu Bakr. Abu Bakar’s leadership succession was based on ethical political principles such as justice, consultation (shura), simplicity, and responsibility. Suggestions for society to adopt and apply these political ethical values ​​in everyday life, both in the personal and professional spheres, to build a more just, transparent and responsible society.